Dynamic Systems Modeling for Sustainable Economic Empowerment in Cilacap - Nurul Anwar; Nita Triana; Dani Kusumastuti (Economic Journal of Emerging Markets, 2009)
This paper investigates the dynamic problem of living system in Kampung Laut, Cilacap, whichincludes social problems and ecological changes. The paper uses a dynamic system model to structurethe problems. The model simulates various feasible scenarios, from which the best becomesthe base to impose a policy to empower their sustainable economy. The model conceptualizes variablesrelated to the problem to build a figure of Causal Loop Diagram (CLD), which is then simulatedusing Powersim 2.5 software package. Using the scenario of intensification and populationcontrol, the paper finds that it can increase the people’s income, with positive trend until the end ofsimulation.Keywords: Dynamic modelling, sustainable economic empowerment, causal loop diagram